Evaluation of Educational Offerings Associated with the 2014 Farm Bill. (13th November 2017) - Ellison, Brenna; Paulson, Nicholas D; Taylor, Mykel R; Tonsor, Glynn T; Coppess, Jonathan; Schnitkey, Gary D
Abstract: The 2014 Farm Bill required farmers and landowners to make a set of one‐time, irrevocable decisions lasting for the duration of the farm bill. The decisions included the choice between three program alternatives with uncertain payments. To aid in making those decisions, the farm bill funded two key educational efforts: ( a ) the development of two online decision tools and ( b ) additional funding to support land grant institutions and extension systems to educate farmers through more traditional extension mediums, particularly in‐person meetings. This paper provides an evaluation of both types of farm bill education through two case studies.